Health-related social media use and COVID-19 anxiety in adolescence: health anxiety as covariate and moderator - Lokajova, Adela; Smahel, David; Kvardova, Nikol (Frontiers in Psychology, 2023)
Background. Adolescents can benefit from health-related content on social media (e.g., related to diseases, prevention or lifestyle). Yet, such content may be distressing, exaggerated and challenging for mental well-being, especially during the pandemic. Rumination about such content may lead to Covid-19 anxiety. Yet, the individual factors that would explain the association between health-related social media use (SMU) and Covid-19 anxiety are understudied. Objective. The current study aimed to fill the gap by investigating the association between health-related SMU and Covid-19 anxiety in the light of several individual factors: health anxiety, eHealth literacy, and mild and severe experience with Covid-19 infection. We studied (1) the relationship between individual factors and health-related SMU, (2) health anxiety as a moderator in the association between health-related SMU and Covid-19 anxiety, and (3) a direct effect of experience with Covid-19 on Covid-19 anxiety. Methods. Using SEM, we analyzed cross-sectional data collected in June 2021 from a representative sample of 2,500 Czech adolescents, aged 11-16, 50% girls. Sociodemographic measures, health-related SMU, Covid-19 anxiety, health anxiety, eHealth literacy and mild and severe experience with Covid-19 infection were assessed with an anonymous online survey. Results. We conducted a path analysis to test the main relationships and additional simple-slopes analysis to explore the moderating effect of health anxiety. Higher health anxiety and eHealth literacy were associated with increased health-related SMU. The effect of experience with Covid-19 infection on both Covid-19 anxiety and health-related SMU was negligible. Health-related SMU and Covid-19 anxiety were positively associated, however only for adolescents high in health anxiety. For other adolescents, the two variables were unrelated. Conclusion. Our findings show that adolescents with higher health anxiety and eHealth literacy engage in health-related SMU more intensively. Furthermore, for adolescents high in health anxiety, the health-related SMU is associated with Covid-19 anxiety. This is likely due to differences in media use, e.g., using social media for content more likely leading to Covid-19 anxiety, compared to other adolescents. We recommend to focus on identification of such content, which may lead to more precise recommendations regarding health-related SMU compared to cut-back on the frequency of overall SMU.